TO THE STUDY OF THE PROCESSES OF CHARGING AND DISCHARGING A CAPACITOR (Web of Technology: Multidimensional Research Journal, 2024)
This article is devoted to the theory of the processes of charging and discharging capacitors, using it as laboratory work, you can experimentally determine the capacitance of the capacitor.